Association of Neonatal AKI with Gestational Age and Birth Weight in Tertiary Care Hospitals of Dhaka City, Bangladesh (Sir Salimullah Medical College Journal, 2023)
Background: Acute kidney injury (AKI) is common in neonatal intensive care unit (NICU) and also in general neonatal ward (GNW) of two tertiary care hospitals (Dhaka Medical College and Sir Salimullah Medical College Mitford Hospital). Association of neonatal AKI with different birth weights (low birth weight, very low birth weight, extreme low birth weight) and gestational age (both term and preterm) has greater impact on AKI. Early detection and immediate management is life saving.Methodology: This prospective observational study carried out in NICU and GNW of DMCH & SSMC Mitoford Hospital over a period of one year to find out the AKI cases within the first 28 days of life. Blood sample collected by plane test tube and send to the laboratory and serum creatinine levels were estimated by auto analyzer (PICTUS-400). AKI was leveled when serum creatinine >1.5 times of medium values. Those AKI patients were evaluated in relation with gestational age & birth weight. After counselling and taking informed written consent from legal guardians, three hundred neonates were enrolled in this study by purposive sampling. The data were collected in a pre-structured questionnaire and analysis by SPSS 22 software.Results: A total of 300 neonates were included in this study. Mean age of the neonates were 5.71±6.70 days (age range 1-28 days). Male were predominant (59.4%). Male and female ratio was 1.46:1. AKI developed in 23.7% neonates. Among them 53.5% was appropriate for gestational age (AGA), 36.6% had LBW and 9.9% had VLBW. Among preterm, term and post term 24.4%, 22.0% and 75.0% developed AKI respectively. Neonatal AKI also associated mostly with perinatal asphyxia (43.8%) and neonatal sepsis (35.21%).Conclusion: AKI developed in 23.7% neonates. AKI prevalence is same in gestational age and birth weight.Sir Salimullah Med Coll J 2023; 31: 73-78